Involvement of splenic dendritic cells during infectious bursal disease virus infection in chickens - Abd Rahman, Yasmin; Bejo, Mohd Hair; Kaiser, Pete; Fakurazi, Sharida; Omar, Abdul Rahman (Faculty of Veterinary Medicine, 2013)

(untitled)
Infectious bursal disease virus (IBDV) is attracted to lymphoid cells and especially those of B-lymphocyte origins. Recent studies have shown that IBDV also can infect macrophage. However, the involvement of dendritic cells (DC) in IBDV infection is not clear. The objective of this study was to examine the effect IBDV vaccine and very virulent (vv) strains on avian derived splenic DC. Enriched DCs were cultured from spleen of infected SPF chickens with vaccine and vvIBDV strains of IBDV. The infected DCs were analysed for morphology study, immunophenotyping, proliferation activity, and immunofluorescent antibody test (IFAT). Both IBDV strains inhibit DC proliferation. However, the inhibition is higher in vvIBDV strain group. However, the expressions of IBDV antigens from both strains were detected in splenic DC.